Sequential co‐infections drive parasite competition and the outcome of infection. Issue 10 (10th August 2020) - Zilio, Giacomo; Koella, Jacob C.
Abstract: Co‐infections by multiple parasites are common in natural populations. Some of these are likely to be the result of sequential rather than simultaneous infections. The timing of the co‐infections may affect their competitive interactions, thereby influencing the success of the parasites and their impact on the host. This may have important consequence for epidemiological and eco‐evolutionary dynamics. We examined in two ecological conditions the effect of sequential co‐infection on the outcome of infection by two microsporidians, Vavraia culicis and Edhazardia aedis, that infect the mosquito Aedes aegypti . The two parasites have different transmission strategies: V. culicis is transmitted horizontally either among larvae or from adults to larvae, while E. aedis can be transmitted horizontally among larvae or vertically from females to their eggs. We investigated how the timing and order of the co‐infection and how the host's food availability affected the parasite's transmission potential (the percentage of individuals that harboured transmissible spores) and the host's juvenile survival, its age at emergence and its longevity. The outcome of co‐infection was strongly affected by the order at which the parasites arrived. In co‐infections, V. culicis had greater horizontal transmission if it arrived early, whereas the transmission potential of E. aedis, either vertical or horizontal, was not affected by the competitor V. culicis . The availability of food determined the duration of infection leading to variation in mortality and in the transmission potential. For both parasites low food decreased juvenile survival, delayed emergence to adulthood and increased horizontal transmission potential. High food increased juvenile survival and the probability of emergence with higher vertical transmission for E. aedis . Overall, our results suggest that early infection favours transmission and that (a) V. culicis plastically responded to co‐infection, (b) E. aedis was not affected by co‐infection but it was more susceptible to factors extending or decreasing the time it spent in the host (time of infection and food). Our results emphasize the complexity of the impact of co‐infection on host–parasite interactions. In particular, the timing and order of sequential co‐infections can result in different within‐host dynamics and modify infection outcomes. Abstract : This empirical study shows the importance of order and time of co‐infection, and that subtle details of how each parasite interacts with its host may have a fundamental role on the outcome of infection (e.g. virulence, transmission), and thus for epidemiology and host–parasite evolution.